Flirting with his forbidden lady - Martin, Laura (Laura Leanne) (Harlequin historicals., 2021)
"Returning from India to a forbidden liaison... Joshua Ashburton hasn't seen his brother for years and heads straight to his London town house. A ball is underway filled with the cream of society, including one Lady Elizabeth Hummingford. Captivated by her vitality and sparkle, he's shocked to learn she's all but engaged to his brother! It's a loveless, convenient match, but how can Josh persuade her she's chosen the wrong brother when he's set to return abroad?"--Provided by publisher.